ANALISIS FRAMING PEMBERITAAN JOKOWI MINTA DIKRITIK DI MEDIA ONLINE TIMES INDONESIA DAN TEMPO.CO (ANALISIS FRAMING BERITA TIMES INDONESIA DAN TEMPO.CO PERIODE FEBRUARI 2023) - Nursitawati Nursitawati; Ari Suseno (Institut Bisnis Muhammadiyah Bekasi, 2023)
Abstract This study, entitled “Analysis of Jokowi's news framing, asked for criticism in the online media Times Indonesia and Tempo.co.”. The purpose of this study is to find out how Times Indonesia and Tempo.co framed Jokowi's news coverage asking for criticism. This study analyzes 4 news units, consisting of 2 news units from Times Indonesia and 2 news units from Tempo.co. In this study, researchers use framing theory where this theory assumes that frames are the way the media and media gatekeepers regulate the presentation of an event and the issues they cover, especially researchers using the framing theory proposed by Zhongdang Pan and Kosicki. The paradigm used in this research is constructivism with qualitative research methods. The results of this study indicate that the two media have very different and even opposite frames. Like Times Indonesia in reporting on Jokowi asking to be criticized, Times Indonesia tending to be less objective in this report, Times Indonesia going too far to heed Jokowi's policies without looking at other aspects that are also related to Jokowi asking for criticism, in contrast to Times Indonesia, Tempo.co in reporting Jokowi asking for criticism tends to try to maintain objectivity but is still embellished with a tendency to accuse Jokowi of being a paradox, but the information provided by Tempo.co is closer to the actual reality. Keywords: Framing, Online Media, Jokowi asks for criticism